Landscape as a support for collectivity on the different scales of inhabitation - Cortés Sánchez, Luis Miguel; Terrados Cepeda, Javier; Savolainen, Panu (Landscape Architecture and Art, 2024)
The landscape is not merely a backdrop to our urban environments, but plays an intrinsic role in fostering collective identity and cohesion. This hypothesis serves as the basis for the research, which aims to investigate how architectural design can not only reflect but also enhance the formation of collective identity. In order to substantiate this hypothesis, an examination will be made of built architectural experiences that have previously addressed this approach. An illustrative example is the Suvikumpu housing complex designed by Raili and Reima Pietilä in the late 1960s in Espoo, Finland. The analysis of the project examines the three scales at which the community shaped the architectural design: the landscape, the neighborhood and the dwelling. This study has shown how the project, as documented in the original graphic design held by the Museum of Finnish Architecture (MFA), begins with the appropriation and reinterpretation of the landscape and its constituent elements, resulting in a design that supports collective living.